Extended Repetitive Transcranial Magnetic Stimulation Therapy for Post-stroke Depression in a Patient With a Pre-frontal Cortical Lesion: A Case Study - Hordacre, Brenton; Chau, Anson; Graetz, Lynton; Hillier, Susan (Frontiers in Neurology, 2022)
Approximately one-third of stroke survivors experience post-stroke depression. Repetitive transcranial magnetic stimulation (rTMS) of the prefrontal cortex has shown promise as a treatment for depression with few side effects and high tolerability. However, previous post-stroke depression trials have not considered the effect of lesion location, the persistence of clinical improvements, nor the value of ongoing maintenance treatments. These questions are important to determine the therapeutic value of rTMS as a treatment for post-stroke depression. We report a unique case study of a 71-year-old male who had experienced a left hemispheric ischemic stroke four years prior. The patient was screened with the Beck Depression Inventory and Patient Health Questionnaire and found to be experiencing moderate levels of depression. Ten daily sessions of left dorsolateral pre-frontal cortex rTMS were applied over a two-week period. A clinically meaningful reduction in depression was achieved. Approximately 10 weeks following rTMS treatment, improvements in depression were attenuating. Weekly maintenance rTMS was delivered to the left dorsolateral pre-frontal cortex for 10 sessions. At the conclusion of maintenance rTMS, clinical assessments indicated depressive symptoms had reduced to a minimal to nil level. Clinically meaningful improvements in depression were maintained at 3 months after rTMS treatment had ceased. These findings provide novel insight to suggest rTMS may reduce depressive symptoms in stroke survivors with a lesion at the site of stimulation. Ongoing maintenance treatments might prove beneficial to enhance persistence of clinical improvements.